Transforming village libraries to enhance community literacy and empowerment in Serengan, Surakarta - Bachrul Ilmi; Rahmat Setiawan Saefullah; Siti Nurkamilah; Katrin Setio Devi; Zahrina Roseliana Mazidah; Rr. Iridayanti Kurniasih; Nurlistiani; Rahmat Fadhli (University of Merdeka Malang, 2025)
Literacy is a crucial factor in improving the quality of human life. The Serengan Village Library in Surakarta City has significant potential as an inclusive and sustainable community-based literacy center. This community service program aims to implement the national Social Inclusion-Based Library Transformation program, with its mission to improve the Community Literacy Development Index. The community service program is implemented through design, outreach, implementation, and monitoring and evaluation. The program includes technology-based library management to improve the competency of librarians (18 participants), School Literacy Movement (GLS) training (20 participants), and digital marketing and product photography training for MSMEs (20 participants). Monitoring and evaluation are conducted using indicators, which include design, action, and indicators. The results of the activities indicate an increase in the capacity of all target groups (librarians, teachers, and communities involved) for the program (220 percent on average from the baseline). These include more professional librarians, more creative teachers in conveying literacy to children, and more digitally prepared MSMEs. This program can be a model to establish the TPBIS program in the other village libraries. Moreover, this program contributes to strengthening the function of village libraries as community literacy centers and supports the achievement of SDG 4 on quality education.